A possible analytical and clinical role of endogenous antibodies causing discrepant adrenocorticotropic hormone measurement in a case of ectopic Cushing's syndrome. (July 2014) - Saiegh, Leonard; Odeh, Majed; Chen-Konak, Limor; Elias, Nizar; Sheikh-Ahmad, Mohammad; Reut, Maria; Slobodin, Gleb; Bejar, Jacob; Shechner, Carmela
Heterophilic antibodies are well described, but poorly appreciated interferents and is often not a recognized problem affecting most immunoassays. We report a patient presented with ectopic Cushing's syndrome (CS), but repeated plasma adrenocorticotropic hormone (ACTH) concentrations conducted by immunoassay were inappropriately within the reference range and not elevated, most probably as a result of antibody interference. A 36-year-old woman, presented with large gastric neuroendocrine carcinoma and severe ectopic CS, while repeated plasma ACTH concentrations conducted by immunoassay were inappropriately within the reference range. As we expected ACTH concentration to be higher, we performed several tests to evaluate whether there was any assay interference causing falsely lower than expected ACTH results. We measured ACTH using a different immunoassay, assayed the sample in dilution, assayed the sample after being incubated in heterophilic antibody blocking agent tube and performed recovery studies. Tests indicated the presence of interfering compounds, most probably heterophilic antibodies. When clinicians find ACTH concentrations to be lower than expected, we recommend the laboratory investigate antibody interference.